Structure and expression of germ line immunoglobulin gamma 2b transcripts. - Lutzker, S (1988)
We have isolated a cDNA copy of a truncated C gamma 2b transcript produced by Abelson murine leukemia virus transformants that spontaneously switch from mu to gamma 2b. The initiation site of this transcript was 2 kilobases 5' to the gamma 2b switch recombination region, demonstrating its germ line origin. Nucleotide sequence analyses suggest that this transcript does not encode a protein. Expression of germ line gamma 2b transcripts in Abelson murine leukemia virus transformants and in normal spleen cells correlated with endogenous gamma 2b class switch activity.